"I wasn't texting; I was just reading an email …": a qualitative study of distracted driving enforcement in Washington State. Issue 3 (15th September 2016) - Nevin, Paul E; Blanar, Laura; Kirk, Annie Phare; Freedheim, Amy; Kaufman, Robert; Hitchcock, Laura; Maeser, Jennifer D; Ebel, Beth E
Abstract : Background: In response to the rise of distracted driving, many countries and most US states have adopted laws to restrict the use of handheld phones for drivers. Specific provisions of each law and the overall social mores of distracted driving influence enforceability and impact. Objectives: Identify multilevel interdependent factors that influence distracted driving enforcement through the perspective of police officers. Design/methods: We conducted focus group discussions with active duty law enforcement officers from three large Washington State counties. Our thematic analysis used descriptive and pattern coding that placed our findings within a social ecological framework to facilitate targeted intervention development. Results: Participants reported that the distracted driving law posed challenges for consistent and effective enforcement. They emphasised the need to change social norms around distracted driving, similar to the shifts seen around impaired driving. Many participants were themselves distracted drivers, and their individual knowledge, attitude and beliefs influenced enforcement. Participants suggested that law enforcement leaders and policymakers should develop and implement policies and strategies to prioritise and motivate increased distracted driving enforcement. Conclusions: Individual, interpersonal, organisational and societal factors influence enforcement of distracted driving laws. Targeted interventions should be developed to address distracted driving and sustain effective enforcement.